BRIDGING CULTURES THROUGH TRANSLATION: THE ROLE OF CULTURAL CONTEXT IN ENGLISH-UZBEK TRANSLATIONS (Лучшие интеллектуальные исследования, 2025)
This article investigates the pivotal role of cultural context in achieving effective English-Uzbek translations. It argues that successful translation transcends mere linguistic conversion, demanding a profound understanding of the source and target cultures' nuances, including idioms, proverbs, social customs, historical allusions, and religious undertones. The study explores the challenges inherent in cross-cultural communication, particularly when dealing with asymmetric cultural concepts that lack direct equivalents. By analyzing specific translation examples, this research highlights how cultural awareness directly impacts accuracy, naturalness, and the preservation of original intent and emotional resonance. The findings underscore the necessity for translators to possess not only linguistic proficiency but also deep intercultural competence to bridge the communicative gap and foster genuine cultural exchange.В данной статье рассматривается ключевая роль культурного контекста в достижении эффективности англо-узбекских переводов. В ней утверждается, что успешный перевод выходит за рамки простой языковой конверсии и требует глубокого понимания нюансов исходной и целевой культур, включая идиомы, пословицы, социальные обычаи, исторические аллюзии и религиозные оттенки. В исследовании рассматриваются проблемы, присущие межкультурной коммуникации, особенно при работе с асимметричными культурными концепциями, не имеющими прямых эквивалентов. Анализируя конкретные примеры перевода, данное исследование показывает, как культурная осведомлённость напрямую влияет на точность, естественность и сохранение первоначального замысла и эмоционального отклика. Результаты подчёркивают необходимость для переводчиков обладать не только лингвистическим мастерством, но и глубокой межкультурной компетенцией для преодоления коммуникативного разрыва и содействия подлинному культурному обмену.